Insulin-like growth factor-I and C-reactive protein during pregnancy and maternal risk of non-epithelial ovarian cancer: a nested case-control study - Toriola, Adetunji T.; Surcel, Helja-Marja; Lundin, Eva; Schöck, Helena; Grankvist, Kjell; Pukkala, Eero; Chen, Tianhui; Toniolo, Paolo; Lehtinen, Matti; Zeleniuch-Jacquotte, Anne; Lukanova, Annekatrin (Cancer causes & control, 2011)
Insulin-like growth factor-I (IGF-I) and C-reactive protein (CRP) may be positively associated with the risk of epithelial ovarian cancer (EOC) but no previous studies have investigated their associations with non-epithelial ovarian cancers (NEOC).